Covid-19 Vaccination as Part of The Basic Right to Health, Should it be Mandatory During The Covid-19 Pandemic - Lefri Mikhael (SASI, 2021)
The 2019 Coronavirus disease virus that shocked the world at the beginning of 2020 as a pandemic had consequences for several sectors of life, especially human health. Health as a fundamental human right that is owned by every human being needs to be considered during the Pandemic. Various efforts have been made by the Government to deal with this situation, one of them is the Covid-19 vaccination. Then, the question is whether the vaccination is optional or mandatory. The research carried out is a normative juridical research with a conceptual approach and a statutory approach related to the Covid-19 vaccination policy and the collection of legal materials obtained through a literature study. In summary, this article explains that the Covid-19 vaccination is part of the fulfillment of the right to health during the Pandemic and it can be said as an obligation for those who are prioritized as vaccine recipients, with the main reason of achieving public health.